Natural instinct and control: The impact of nature and society on LGBT practitioners: The view of a former LGBT practitioner - Owoyemi, Musa Yusuf; Ahmad Sabri, Ahmad Zaharuddin Sani (MAXWELL Science Publication, 2013)
This study discusses the view of a former LGBT practitioner on whether this sexual orientation is natural,controllable and how people who are involved in it relate with the larger society.The idea is to bring to fore the role that nature plays in the LGBT issue, how it could be controlled and also to take a peep at the social life of the practitioners of this sexuality.In order to properly bring his experience to the fore, the paper uses the interview method to gather information from an experienced former practitioner of this sexual orientation and further analyze the information using content analysis format.